MORAL DILEMMAS AND RELATIONAL ETHICS: A STUDY OF DESHPANDE’S THE DARK HOLDS NO TERRORS - Ishika Gupta; Mary Hephzibah (PT. Antis International Publisher, 2026)
Objective: The study analyzes the ethical journey of the female protagonist in Shashi Deshpande's The Dark Holds No Terrors (1980), focusing on her moral conflicts and relational ethics. Using Carol Gilligan's theory of moral development, the research aims to explore how patriarchal structures influence the protagonist’s moral choices. Method: The research employs Carol Gilligan’s theory of moral development to analyze the ethical struggles and moral growth of the protagonist, particularly her challenges in balancing family obligations, societal expectations, and personal autonomy. Results: The study identifies the key stages where the protagonist faces significant resistance in progressing to the next stage of moral development. It also examines how her relationships with family, partner, and society shape her ethical decisions. Novelty: The research highlights the interplay between moral dilemmas and relational ethics in Indian English literature, offering new insights into how societal expectations and family dynamics impact the moral development of women.